Comparative Effects of Iron Chelators on the Transfusion-Dependent Beta-Thalassemia Patients (TAJ: Journal of Teachers Association, 2018)
This prospective study assessed the quality of life of patients with transfusion-dependent beta-thalassemia receiving three different iron chelation treatments. Patients enrolled were receiving one of the following chelation therapies: Group-I: deferoxamine (n=21), Group-II: deferasirox (n=75) and Group-III: deferoxamine in combination with deferiprone (n=39). The three groups were compared in terms of their quality of life, satisfaction and adherence to treatment, control of their health, and self-esteem through the completion of five questionnaires. A higher percentage of patients receiving deferoxamine felt that their treatment negatively influenced their body and skin appearance and limited their ability to work, attend school, and perform daily tasks (P=.0.0066). The adherence to treatment rate and self-esteem were the lowest in the deferoxamine group (P